Application of molecular markers (RAPD, AFLP and Microsatellites) to Iberian pig genotype characterization - Ovilo C.; Barragán M.C.; Castellanos C.; Rodríguez M.C.; Silió L.; Toro M.A. (Tradition and innovation in Mediterranean pig production, 2000)
Use of molecular markers is specially interesting for the genetic study of the Iberian pig, whose morphologic and physiologic variability prevents the knowledge of his populational structure. Crossbreeding, mainly with Duroc, is a common practice to increase the carcass performance which leads to the attainment of worse quality cured products. Molecular analysis techniques allow the estimation of genetic variability and divergence between species and populations, and thus they can be used for phylogenetic studies, conservation programs and control of the genetic origin of products. This work presents the results obtained with the application of three different techniques of DNA polymorphisms detection to samples from different populations of Iberian pigs. The RAPD technique was used for the identification of diagnostic markers which allowed the detection of Duroc genes in Iberian pig samples. AFLP technique was used for the attainment of specific markers of one Iberian pig population, with a high inbreeding level, in order to study its possible utilization in a conservation program. Finally, seven populations have been analysed with 19 microsatellite markers. The analysis of these polymorphic loci genotypes enabled the estimation of different parameters of genetic diversity (heterozygosity, genetic distances).
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)